1998
DOI: 10.1097/00007632-199801010-00018
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography-Guided Biopsy of the Spine

Abstract: Computed tomography-guided biopsy is an important tool in the evaluation of spinal lesions. A positive biopsy result may preclude the need for open surgical intervention. This study included one of the largest series of patients in the medical literature. In addition, it determined the diagnostic rates of this procedure with respect to the major influencing variables. Thoracic-level biopsies have a diagnostic rate that is significantly lower than that of other spinal levels. No significant correlation was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
2
4

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(60 citation statements)
references
References 15 publications
1
53
2
4
Order By: Relevance
“…Also, with regard to biopsy, computed tomography-guided needle biopsy may be optimal to prevent contamination of tumor tissue. 33 In the current series, overall survival for patients who underwent either intralesional surgery or no surgery and received adjunctive irradiation was better compared with overall survival for patients without this modality, a phenomenon similar to that reported by Shives et al 5 Sundaresan et al 25 also suggested that the combination of complete tumor resection (spondylectomy) with chemotherapy and radiation may increase survival. In their report, three patients who underwent surgical tumor resection and irradiation with chemotherapy survived longer than 36 months without evidence of disease.…”
Section: Discussionsupporting
confidence: 85%
“…Also, with regard to biopsy, computed tomography-guided needle biopsy may be optimal to prevent contamination of tumor tissue. 33 In the current series, overall survival for patients who underwent either intralesional surgery or no surgery and received adjunctive irradiation was better compared with overall survival for patients without this modality, a phenomenon similar to that reported by Shives et al 5 Sundaresan et al 25 also suggested that the combination of complete tumor resection (spondylectomy) with chemotherapy and radiation may increase survival. In their report, three patients who underwent surgical tumor resection and irradiation with chemotherapy survived longer than 36 months without evidence of disease.…”
Section: Discussionsupporting
confidence: 85%
“…In the past, lower accuracy rates have been reported for CT-guided needle biopsies at the thoracic spine [9]. In our study however, accuracy rates were higher in the thoracic, lumbar and sacral tracts, and whereas the cervical tract has the lowest.…”
Section: Discussioncontrasting
confidence: 73%
“…In case of deep lesions, for example in the pelvis or spine, needle biopsies are challenging procedures [16]. In these cases, the aid of computed tomography (CT)-guidance has further increased accuracy, reduced complications and therefore has now become the procedure of choice [5,8,9,11,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In the study conducted by Kornblum et al 9 in 1998, it was reported that with computed tomography (CT)-guided biopsy adequate specimens were obtained in 87% of cases. On the other hand, adequate sample were obtained in all the cases of this study.…”
Section: Discussionmentioning
confidence: 99%